Combined endovascular and surgical resection of a giant lumbosacral arteriovenous malformation in a patient with Cobb syndrome. (6th April 2011) - Spiotta, Alejandro M; Hussain, Muhammad Shazam; Masaryk, Thomas J; Krishnaney, Ajit A
Abstract : Objective and importance: Cobb syndrome is a rare condition that includes a cutaneous nevus with an associated spinal vascular lesion at the same dermatome. We present a challenging case of a progressively symptomatic massive lumbosacral arteriovenous malformation (AVM) in a patient with Cobb's syndrome requiring a multimodality approach including staged preoperative transarterial and transvenous endovascular embolization followed by surgical excision and wound reconstruction. Clinical presentation: The patient presented with a massive lumbosacral AVM with symptoms of congestive heart failure. Angiography demonstrated arterial feeders predominantly from internal iliac, median sacral and lumbar segmental arteries. Intervention: The patient underwent staged transarterial and transvenous endovascular embolization resulting in 90% reduction in the AVM size, followed by surgical resection of the lesion. The patient made an excellent recovery with improvement in his symptoms of congestive heart failure. Conclusion: The treatment algorithm for massive AVMs must be individualized. A combination of staged embolization and subsequent surgery may be required to obtain a good result. Through this carefully planned multidisciplinary approach a previously incurable lesion in this patient with Cobb syndrome was able to be treated successfully.